FEATURES OF TRANSFORMATION OF ELECTORAL SYSTEM OF UKRAINE IN THE CONDITIONS OF DEMOCRATIZATION - Іванова, Н.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
The problem of study of dynamics of change of the electoral system of Ukraine and prospects of its transformation is probed. Considerable attention is spared consideration of the basic stages of becoming and development of the Ukrainian electoral system, directions of its change. The prospect of transformation of the mixed electoral system is analysed on the proportional electoral system with the opened lists on conditions of democratization.